Primogeniture - C. Y. Cyrus Chu (Journal of Political Economy, 1991)
On the basis of anthropologists' area-specific research of primogeniture, I propose a Becker-Barro type of dynastic model in which primogeniture may emerge as family heads' optimal policy to minimize their respective lineal extinction probability. I show that parents' bequest division will be affected by the intrinsic mobility structure of the society, contrary to previous causality conjecture. Although an unequal division of bequests widens the within-generation inequality, it may increase the intergenerational upward mobility for the well-endowed child, which in turn improves the originally rigid upward mobility of the poor and middle-income groups and, as a result, reduces the steady-state income inequality.